968 views
2 votes
In the equation t = d/6+3 what is the value of t when d =12

User Lgoncalves
by
5.9k points

2 Answers

2 votes
So you know d= 12
Therefore, you sub it into the equation which will be:
t= 12/6 +3
Using bedmas we know we divide first, 12/6 is 2, therefore that will be 2, then you add that to 3 and you get 5.
t= 5
User Frederik Aalund
by
5.6k points
4 votes
t=d/6+3
1. Fill in: t=12/6+3
2. Remember PEMDAS!! P(parenthesis)E(Exponents)M(multiply)D(divide)A(add)S(subtract)
So, you will divide 12 by 6 first, which equals out to 2.
3. Write your new equation: t=2+3
4. Add 2+3, which equals to 5.

t=5
User Joby
by
5.3k points